The Influence of Motivation, Compensation, and Work Discipline on Employee Performance at PT. Sedayu Cahaya Perkasa - Yasmin Miranti; Muhammad Yalzamul Insan; Emi Wakhyuni (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
The fast expansion of digital infrastructure requires both advanced technology and optimal human resource performance. The primary objective of this research is to explore how motivation, compensation, and work discipline shapes the performance of employees at PT. Sedayu Cahaya Perkasa. This study utilises a quantitative approach with 53 participants, and data gathering involves the distribution of surveys among the company's employees. Data analysis is conducted using the Partial Least Squares (PLS) method, supported by SmartPLS 4 software. The findings suggest that motivation has a significant and positive correlation with employee performance. Similarly, compensation has a notable and affirmative impact on employee performance. Additionally, the study reveals that work discipline also plays a crucial role in enhancing performance. Together, motivation, compensation, and work ethic contribute to 90.3% of employee performance (Adjusted R Square = 0.903), while the remaining 9.7% is influenced by undisclosed factors. The findings shed light that organizations can improve productivity by encouraging intrinsic motivation, fair compensation, and effective work discipline.